Matrix polarization lidar for studying the Asian dust: optimal design and calibration problem - Volkov, Sergey N. физик (Proceedings of SPIE)
The results of experimental determining the morphological and other optical characteristics of the Asian dust show the crucial role of measuring the scattering matrix of particles using a polarization lidar. The accumulated experience of polarization measurements allows the matrix polarization lidar to be designed optimally and the calibration problem to be formulated and solved. Optimality is understood here as simplifying the unit changing the lidar phase plates from four to one plate in the transmitter and receiver. To provide the transition to angular phase plate rotations, the problem of the optimal set of the phase plate states and the problem of measurement sample size are solved. The problem of calibration of the optimal polarization lidar is considered